2015
DOI: 10.1080/09168451.2014.993356
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the antibacterial action of epigallocatechin gallate (EGCg) on Bacillus subtilis

Abstract: Catechins are a class of polyphenols and have high anti-bacterial activity against various microorganisms. Here, we report the mechanism for antibacterial activity of epigallocatechin gallate (EGCg) against Gram-positive bacteria Bacillus subtilis, which is highly sensitive to EGCg. Transmission electron microscope analysis revealed that deposits containing EGCg were found throughout the cell envelope from the outermost surface to the outer surface of cytoplasmic membrane. Aggregating forms of proteins and EGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…Once a membrane effect is known to exist, specific binding assays (Nakayama et al, 2015) or model membrane insertion assays (Wu et al, 2013a) can confidently test direct interactions between specific components. Model membranes have already been used to test the direct interaction of epicatechin gallate and epigallocatechin gallate with membranes (Hashimoto et al, 1999; Kumazawa et al, 2004).…”
Section: Membrane Disruption By Phenolic Compoundsmentioning
confidence: 99%
“…Once a membrane effect is known to exist, specific binding assays (Nakayama et al, 2015) or model membrane insertion assays (Wu et al, 2013a) can confidently test direct interactions between specific components. Model membranes have already been used to test the direct interaction of epicatechin gallate and epigallocatechin gallate with membranes (Hashimoto et al, 1999; Kumazawa et al, 2004).…”
Section: Membrane Disruption By Phenolic Compoundsmentioning
confidence: 99%
“…GTPs and EGCG have a broad antimicrobial spectrum and inhibit the growth of many foodborne pathogenic and spoilage bacteria [4, 11]. Several studies have indicated that the antibacterial activity of EGCG is due to damage to the bacterial cell membrane, such as peptidoglycan [12], outer membrane proteins [13] and lipid bilayers [14]. Moreover, numerous key enzymes in bacterial cells have been suggested as the targets of EGCG, including FabG and FabI reductases [15], the DNA gyrase B subunit [16], thioredoxin, and thioredoxin reductase [17].…”
Section: Introductionmentioning
confidence: 99%
“…Two different commercially available botanical formulations which contain Juglans nigra were also recently shown to have activity against log phase spirochetes of B. burgdorferi strain GCB726, round bodies and biofilm formation in in vitro testing (64). Juglans nigra has also been shown to have multiple constituents (65) with antimicrobial properties including juglone (5-hydroxy-1,4naphthalenedione), phenolic acids, flavonoids, and catechins (including epigallocatechin gallate) (66,67). Further studies are needed to elucidate which constituents have anti-borrelial activity.…”
Section: Discussionmentioning
confidence: 99%